STUDI LITERATUR FAKTOR KEBERHASILAN TATA KELOLA ORGANISASI BERDASARKAN PERATURAN INTERNAL RUMAH SAKIT - Ahid Nur Hidayati; Bagus Aprianto; Novita Dwi Istanti (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
There are several factors in the hospital by laws that aim to realize an effective, efficient and accountable hospital organization to achieve the hospital's vision and mission to create success in good organizational governance. This study uses a literature search method. Search to get research articles using online databases through Google Scholar, and Garuda. The resulting articles were selected based on publications published between 2011 until 2021. The results of this study were found two factors that affect good organizational governance, which are juridical factors and technical factors. These factors also need to be supported by the principles of hospital governance.